Standardization of a flow cytometric technique for detection of anti-sperm antibodies in bulls. - Sardoy, Maria Clara (Kansas State University, 2011)
Presence of anti-sperm antibodies (ASA) is associated with infertility in many species, including bulls but there is no standardized direct technique that allows detection of ASA bound to the sperm surface. The overall objective was to standardize a flow cytometric technique for detection of IgG and IgA directly attached to bovine sperm. The effects of fixation using phosphate buffer solution (PBS) or diluted formalin buffer solution (dFBS), exclusion of dead cells from the analysis, and aliquot variability were assessed using healthy bulls classified as Satisfactory Potential Breeders (SPB, n=9) and bulls with experimentally induced ASA (n=4) (Experiment1). The effect of freezing on the percentage of IgG- and IgA- bound sperm was assessed in samples from immunized bulls (n=4) (Experiment 2). Anti-sperm antibodies on the sperm surface were induced in yearling bulls by intramuscular injection of autologous semen and an adjuvant. Fixation of sperm cells did not affect the percentage of IgG- or IgA-bound sperm in any group of bulls. Exclusion of dead cell from the analysis did not affect the percentage of IgG-bound sperm (p= 0.0922 and p= 0.1525 for immunized and reproductively normal bulls, respectively). The exclusion of dead cells significantly increased the percentage of IgA-bound sperm in semen samples from immunized bulls (p= 0.0152) and significantly decreased the percentage of IgA- bound sperm in semen samples from reproductively normal bulls (p= 0.0012). Variability was < 10% in samples from immunized and reproductively normal bulls for percentage of IgG- and IgA-bound sperm. Freezing did not affect the percentage of IgG- (p=0.1287) or IgA-bound sperm (p=0.4175). Based on these results, fixation is neither necessary nor detrimental for analysis, and the percentage of antibody-bound cell should be calculated gated on the population of live cells only, especially when evaluating IgA binding. The percentage of ASA-bound sperm can be assessed on frozen-thawed samples. The development of this technique allows for further studies on ASA-bound sperm in populations of normal and abnormal bulls.
Keywords: Antisperm antibodies; Bull infertility; Flow cytometry; Frozen semen; Animal Sciences (0475); Veterinary Medicine (0778)